More than 1300 Food System Actors in seven countries engaged in the cocreation of agroecological innovations for promoting effective and sustainable agroecological transitions in the first year of implementation of the CGIAR initiative on Agroecology - Staiger Rivas, Simone (2023)
The CGIAR initiative on Agroecology established Agroecological Living Landscapes (ALL) in seven countries. Jointly, members of those territories who act along the food value chain assess and demonstrate which agroecological innovations work best, where, why, and for whom. They identify business opportunities and financial mechanisms for local enterprises to deal with agroecological innovations. They develop context-specific strategies and action plans that encourage and support sustainable behavior change, and they determine the most suitable policies and mechanisms of policy integration for promoting effective and sustainable agroecological transitions. In only one year more than 1300 actors are actively engaged in co-innovation processes.